Scientific activity of Ukraine in Antarctica in the next decade - P. F. Gozhyk; V. Litvinov; V. M. Malanchuk (Ukrainian Antarctic Journal, 2010)
In November, 2010, the Cabinet of Ministers of Ukraine adopted Resolution # 1002 "On the Confirmation of the State Target Scientific Technical Program for Research in the Antarctic in 2011-2020". The Resolution not only opens new ways for our scientists for both research and further consolidation as a leading team exploring the continent, but also ties in with Ukraine's international obligations as part to the Antarctic Treaty of 1959. Here we review the program's main avenues of research and their possible implementations.